PENGARUH EKSTRAK DAUN PEDADA (Sonneratia alba) TERHADAP MUTU UDANG API-API (Metapenaeus monoceros) PASCA PANEN - Rizal, Samsu; Asiki, Andi Noor; Saptiani, Gina (UNIVERSITAS MUHAMMADIYAH MATARAM, 2021)
Shrimp is a leading commodity traded in local and international markets. The process of deterioration of shrimp quality can be caused by an autolysis reaction. This problem is the rationale for looking for an alternative natural preservative that is harmless and easy to obtain, namely using pedada (S. alba) leaves. This study aimed to determine the effect of pedada leaf extract (S. alba) on the post-harvest quality of fire shrimp and to determine the best concentration in inhibiting bacterial growth during cold storage (5oC). The test parameters observed were TPC, pH, and organoleptic tests. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. The treatments consisted of P1 (seawater extract + 800 ppm S. alba); P2 (seawater extract + S. alba 1200 ppm); P3 (freshwater extract + S. alba 800 ppm); P4 (freshwater extract + S. alba 1200 ppm); and P5 (control/without extract). The results showed that the immersion of fire shrimp in pedada leaf extract did not affect the TPC and pH values during cold storage, but did affect the organoleptic test for the appearance, smell, and texture specifications of the shrimp. Pedada leaf extract with 1200 ppm seawater as a solvent during cold storage (5°C) obtained the best results with a TPC value of 2.88 log cfu/g, a pH value of 7.12, and an organoleptic value (appearance 7.3, odor 7.3 and texture 7,3).